Diagnostic Role of Carotid Intima-Media Thickness for Coronary Artery Disease: A Meta-Analysis. (27th February 2020) - Liu, Dianmei; Du, Caiju; Shao, Weiguang; Ma, Guifeng
Abstract : Background . The present meta-analysis was conducted to confirm whether carotid intima-media thickness (IMT) could serve as an accurate diagnostic method for coronary artery disease (CAD). Methods . Databases of PubMed, Google Scholar, and Embase were searched for potential articles. The articles were selected according to inclusion criteria. Pooled sensitivity and specificity with corresponding 95% confidence interval (CI) were used to confirm the diagnostic role of IMT for CAD. I 2 and P value were used to assess the existence of heterogeneity. I 2 ≥ 50 % or P < 0.05 indicated significant heterogeneity. Area under the curve (AUC) of summary receiver operating characteristics (SROC) represented the diagnostic accuracy of IMT. Sensitivity analysis was performed to evaluate the robustness of pooled outcomes. Deek's funnel plot was drawn to detect potential publication bias. Results . 22 eligible articles were selected in the present meta-analysis. Pooled sensitivity and specificity of IMT for diagnosing CAD were 0.68 (0.57–0.77) and 0.70 (0.64–0.75), respectively. The corresponding AUC was 0.74 (0.70–0.78). Subgroup analyses based on cutoff value of IMT were performed. A cutoff value of 1 mm was demonstrated to be much more accurate diagnostic criteria for CAD (sensitivity: 0.66; specificity: 0.79; AUC: 0.80). Sensitivity analysis indicated that the pooled results were robust. Deek's funnel plot indicated no significant publication bias (P = 0.195 ). Conclusion . Carotid IMT may serve as an accurate diagnostic tool. A cutoff value of 1 mm seems to provide much more accurate diagnostic results for CAD.